Backtracking search algorithm in CVRP models for efficient solid waste collection and route optimization - Akhtar M.; Hannan M.A.; Begum R.A.; Basri H.; Scavino E. (Elsevier Ltd, 2023)
Bins; Budget control; Carbon dioxide; Cost reduction; Costs; Crashworthiness; Efficiency; Environmental impact; Fuels; Learning algorithms; Optimization; Solid wastes; Vehicle routing; Backtracking search algorithms; Capacitated vehicle routing problem; Environmental emissions; Optimization modeling; Route optimization; Solid waste collection; Threshold waste level; Waste collection; Waste management; fuel; carbon dioxide; solid waste; algorithm; fuel consumption; modeling; optimization; solid waste; threshold; waste management; algorithm; Article; backtracking search algorithm; capacitated vehicle routing problem model; carbon footprint; controlled study; environmental impact assessment; feasibility study; limit of quantitation; measurement precision; process model; process optimization; solid waste collection; solid waste management; motor vehicle; procedures; solid waste; theoretical model; waste disposal; Algorithms; Carbon Dioxide; Models, Theoretical; Motor Vehicles; Refuse Disposal; Solid Waste